Zone 2 intensity: A critical comparison of individual variability in different submaximal exercise intensity boundaries - Meixner, B.; Filipas, L.; Holmberg, H.-C.; Sperlich, B. (Translational Sports Medicine, 2025)
Introduction: Endurance athletes often utilize low-intensity training, commonly defined as Zone 2 (Z2) within a five-zone intensity model, for its potential to enhance aerobic adaptations and metabolic efficiency. This study aimed at evaluating intra- and interindividual variability of commonly used Z2 intensity markers to assess their precision in reflecting physiological responses during training.